CONDENSATION OF COLD NEUTRONS – IDEA OF G.A.GAMOW. CHEMICAL PROPERTIES OF THE NEUTRON MATTER AND ITS PLACE IN THE PERIODIC SYSTEM OF ELEMENTS - Ryazantsev, G. B.; Lavrenchenko, G. K.; Beckman, I. N.; Buntseva, I. M.; Nedovesov, S. S. (Одеські астрономічні публікації, 2018)
Today, the neutron matter and neutron stars are already substantially rooted in the nuclear physics and astrophysics, and it is logical to have their consideration of them in terms of chemical properties and principles of general chemistry. The formation of a neutron substance, in addition to gravitational neutronization, is considered, other mechanisms, such as the condensation of ultracold neutrons (UCN) and neutronization due to a critical increase in the atomic number in the periodic table (PS). The stability of the neutron substance is substantiated already at the micro level due to Tamm interaction and not only at the macro level due to the gravitational interaction, as it is now considered in astrophysics. A neutron substance is a very concrete physical reality, urgently demanding its rightful place in the PS and studying not only physical, but also chemical, and possibly even in the near future, engineering and technical properties. We also consider the possibility of a "chemical" interaction of UCN with molecules of substances with an odd number of electrons. It is proposed to extend the PS beyond the limits of classical chemical substances and to cover a much wider range of matter in the universe, based on the forgotten ideas of D.I. Mendeleev. Moreover, PS begins with neutron and its isotopes (dineutron, tetraneutrone, etc.) and ends the neutron stellar substance.